2006
DOI: 10.1089/apc.2006.20.183
|View full text |Cite
|
Sign up to set email alerts
|

A Faculty Trainer Model: Increasing Knowledge and Changing Practice to Improve Perinatal HIV Prevention and Care

Abstract: Although routine counseling and HIV testing of pregnant women is recommended, it is not yet universally offered. This paper reports on a project that trained health care providers from 2000 to 2002 using a faculty trainer (or train-the-trainer) model. The goals of the projects were to increase knowledge and change practice, increase HIV counseling and testing in prenatal care, and improve management of HIV in pregnant women. In four jurisdictions of the southeastern United States, 193 health care providers att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…[7][8][9][10] The train-the-trainer model has been increasingly used in the education of students in the healthcare professions [11][12][13][14][15][16] and for continuing education of licensed clinicians. [17][18][19][20] The approach appears to be useful in meeting the educational needs of the health care system by increasing the knowledge and skills of providers. Furthermore, staff development programs may improve employee retention.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The train-the-trainer model has been increasingly used in the education of students in the healthcare professions [11][12][13][14][15][16] and for continuing education of licensed clinicians. [17][18][19][20] The approach appears to be useful in meeting the educational needs of the health care system by increasing the knowledge and skills of providers. Furthermore, staff development programs may improve employee retention.…”
Section: Introductionmentioning
confidence: 99%
“…Some components of the TTT structure and delivery that were key to this success included faculty support and technical assistance, financial support and organizational support, similar to other experiences reported in the literature. For example, Burr et al 15 found that ongoing faculty support was a key element of success in their TTT program to reduce perinatal HIV transmission. Other TTT evaluations have found that financial support to obtain items such as training supplies, binders, food, and transportation made an important difference for local trainers.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] In HIV care, TTT strategies have been used primarily for education and prevention. TTT programs have trained health care providers to increase HIV counseling and testing of pregnant women, 15 to train military medical technicians about HIV prevention, 16 to train volunteers in HIV prevention, 17 and to train community health workers to conduct HIV counseling and testing in the Caribbean. 18 Most TTT strategies for HIV care and treatment described in the literature have trained clinicians, primarily doctors and nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…awareness and knowledge of specific health care conditions [7,11,12]. However, formalized TTT programs for nurses about breast health and breast cancer education in Turkey are nonexistent and this TTT National Breast Health program was developed to address the lack of trained health personnel and to provide a very important contribution to breast health and breast cancer patient care quality in Turkey.…”
mentioning
confidence: 99%